Effects of HIF-1α on renal fibrosis in cisplatin-induced chronic kidney disease. Issue 10 (28th May 2021) - Zhao, Hao; Han, Yachun; Jiang, Na; Li, Chenrui; Yang, Ming; Xiao, Ying; Wei, Ling; Xiong, Xiaofen; Yang, Jinfei; Tang, Chengyuan; Xiao, Li; Liu, Fuyou; et al.
Abstract: Cisplatin (Cis) can cause chronic kidney disease (CKD) and promote renal fibrosis, but the underlying mechanism is not fully understood. Hypoxia inducible factor-1α (HIF-1α) can promote renal fibrosis in some kidney diseases, but its role in Cis-induced CKD is still unknown. Notch-1 is a recognized molecule that promotes renal fibrosis under pathological circumstances, and evidence shows that HIF-1α and Notch-1 are closely related to each other. In the present study, mice with HIF-1α gene knockout in proximal tubular cells (PTCs) (PT-HIF-1α-KO) were generated and treated with Cis to induce CKD. A human proximal tubular cell line (HK-2) and primary mouse PTCs were used for in vitro studies. The results showed that HIF-1α was increased in the kidneys of Cis-treated wild-type mice, accompanied by elevated Notch-1, Notch-1 intracellular domain (N1ICD), Hes-1 and renal fibrosis. However, these alterations were partially reversed in PT-HIF-1α-KO mice. Similar results were observed in HK-2 cells and primary mouse PTCs. In addition, treating the cells with Cis induced a marked interaction of HIF-1α and N1ICD. Further inhibiting Notch-1 significantly reduced cellular fibrogenesis but did not affect HIF-1α expression. The data suggested that HIF-1α could promote renal fibrosis in Cis-induced CKD by activating Notch-1 both transcriptionally and post-transcriptionally and that HIF-1α may serve as a potential therapeutic target for Cis-induced CKD.